THE ROLE OF ISLAMIC BOARDING SCHOOLS AS A PART OF THE HALAL ECOSYSTEM IN THE DEVELOPMENT OF A HALAL INDUSTRIAL AREA IN MADURA (International Conference on Social and Islamic Studies, 2022)
Since the Law on Halal Product Guarantee No. 33 of 2014 concerning the guarantee of halal products was ratified, starting to expand community activities in realizing government policies until the issuance of PP No. 39 of 2019 concerning the implementation rules of the law on halal assurance products. We can see from various aspects of activities, both educational activities, the establishment of halal inspection institutions, halal centers both in universities and religious organizations (mandate of the JPH Law). Through this implementation, ideas developed in the development of the halal industry in Indonesia. Some parts of the halal ecosystem have several elements, one of which is education, both formal and non-formal. Madura as one of the islands whose area is known for many Islamic boarding schools so that the role of Islamic boarding schools is one of the potentials that must be prepared properly and professionally in the development of halal industrial areas. The role of the Islamic boarding school is very strong with the role of the caretaker of the Islamic boarding school as a very important figure in every local government. Qualitative methods with an empirical approach are used in extracting primary data, so that it can be maximized. In data analysis, we can conclude that Islamic boarding schools in Madura play an active role in regional development, so there needs to be readiness in empowering Islamic boarding schools from all aspects of governance management including elements of education, economics, and professional human resources. So Islamic boarding schools as part of the halal ecosystem must be ready and welcome the development of a halal industrial area in Madura.